DELIRIUM PADA PASIEN RAWAT INAP DENGAN SKIZOFRENIA: SEBUAH LAPORAN KASUS - Dwi Pradnyawati, Made Ayu; Ratep, Nyoman; Westa, Wayan (E-Jurnal Medika Udayana, 2014)
Delirium is psychiatric disorder characterized by conciousness state impairment, disorientation, and affective alteration, including cognitive and non-cognitive deficite, and developed in acute onset. Delirium stand in organic mental disorder group, which has many similarity of signs and symptoms with psycotic mental disorder as schizophrenia. Delirium, particularly that is not related with alcohol and drug abuse, frequently found in elderly. Some cases of delirium among inpatient psychiatric patients have been reported, but just few further studies have been held on those cases. This case report try to deliver a case of delirium in a 65 y.o. inpatient paranoid type schizophrenia. This patient showed sign of severe disorientation during his treatment. In psychiatric assesment, stated male patient with inappropriate appearance, contact avoidance, decrease of conciousness, and severe disorientation. Mood/affect found irritable/appropriate. Patient experienced delution and hallucination. He suspected with undetected dementia as underlying disease.
Keywords: Delirium, inpatient, dementia